1986
DOI: 10.1159/000183977
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Dialysis and Transplantation in Patients with End-Stage Renal Failure from Hypernephroma

Abstract: We analyzed long-term, 2- to 9-year results and risk factors in 13 patients treated with dialysis and transplantation for hypernephroma. Eight were dialyzed only, 6 died, 4 of them from metastatic disease that occurred in less than 8 months in 3. Five patients were also transplanted. Three died, 1 of metastatic disease. Two are alive, 1 with metastatic disease, 6 years after transplant, 3 years after diagnosis of metastasis. There were no differences in age and sex in those with early metastatic disease when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…11], although this has not been substantiated. Furthermore, some authors have reported post-transplant malignancies regressing with the discontinuation of im munosuppressive therapy [12], but this carries the risk of graft loss. This option of withholding/reducing immuno suppressive therapy to control the cancer with the possi bility of graft loss was explained to our patient who, how ever, refused this line of management since he had had previously numerous complications of dialysis and was not keen on facing the consequences of graft loss.…”
Section: Discussionmentioning
confidence: 99%
“…11], although this has not been substantiated. Furthermore, some authors have reported post-transplant malignancies regressing with the discontinuation of im munosuppressive therapy [12], but this carries the risk of graft loss. This option of withholding/reducing immuno suppressive therapy to control the cancer with the possi bility of graft loss was explained to our patient who, how ever, refused this line of management since he had had previously numerous complications of dialysis and was not keen on facing the consequences of graft loss.…”
Section: Discussionmentioning
confidence: 99%
“…Stewart et al 27 reported an elevated risk for renal parenchymal cancer in patients undergoing dialysis. However, Mandel and Kjellstrand 20 concluded that RCC is an unusual cause of ESRD, occurring in only 0.1%–1% of patients treated by dialysis or transplantation. Epidemiological and clinical evidence has shown links between hypertension, diabetes, obesity, and metabolic syndrome with the onset and progression of chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many patients undergoing renal transplantation experience graft failure and then require long‐term dialysis therapy or renal re‐transplantation. Patients prefer renal re‐transplantation over long‐term dialysis therapy . Renal re‐transplantation presents new complex issues, such as whether an allograft nephrectomy (AN) should be performed in an asymptomatic failed allograft recipient, for patients and health care providers.…”
mentioning
confidence: 99%